MULTISTABLE NETWORKS OF TOPOLOGICAL DEFECTS - HARKAI, SAŠA; KRALJ, SAMO (Anali PAZU, 2023)
Topological defects are a consequence of symmetry-breaking phase transitions and are ubiquitous in nature. An environment where they most easily studied, are nematic liquid crystals. We describe nematic structures at the mesoscopic scale with a tensor order parameter and we determine equilibrium states by numerically minimizing free energy. We enforce defects through boundary conditions at enclosing surfaces. First we show that there are multiple equilibrium states possible by just enforcing one defect, depending on the thickness of the cell. While enforcing multiple defects at the bottom surface we can create equilibrium states with “chargeless” line defects. By enforcing a 4x4 network of defects we can create complex patterns of chargeless line defects, where 18 are quantitatively and 7 are qualitatively different. We also demonstrate how to rewire the line defects to transition from one pattern to another and back. Our system could lead to multistable optical displays and rewirable nanowires.
Keywords: liquid crystal; nematics; topological defects; networks; symmetry